Rediscovery of the Earless Microteiid Lizard Anotosaura collaris Amaral, 1933 (Squamata: Gymnophthalmidae): A redescription complemented by osteological, hemipenial, molecular, karyological, physiological and ecological data - Rodrigues, Miguel Trefaut; Jr, Mauro Teixeira; Vechio, Francisco Dal; Amaro, Renata Cecília; Nisa, Carolina; Guerrero, Agustín Camacho; Damasceno, Roberta; Roscito, Juliana Gusson; Nunes, Pedro M. Sales; Recoder, Renato Sousa (Zootaxa, 2013)
More than a century after its discovery by Ernest Garbe, and almost 80 years after its original description, we obtained a series of specimens of the earless gymnophthalmid Anotosaura collaris, the type species of the genus, up to now known only by a single specimen. On the basis of the material obtained at and close to the type locality we redescribe the species, adding information about the external and hemipenial morphology, osteology and karytoype. Molecular data confirm its sister relationship with Anotosaura vanzolinia as well as the close relationship of Anotosaura with the Ecpleopodini Colobosauroides and Dryadosaura. We supplement this information with thermophysiological, ecogeographical, karyotypic and ecological data.